Effective ways to retain first‐time blood donors: a field‐trial study. Issue 9 (19th June 2019) - Hashemi, Shirin; Maghsudlu, Mahtab; Nasizadeh, Soheila; Esmaielifar, Gilda; Pourfathollah, Ali Akbar
Abstract : BACKGROUND: Regular blood donors are the cornerstone of blood safety. Understanding the donors' behavior to donate blood improves blood donor retention programs. The purpose of this study is to evaluate the return rate of first‐time blood donors following different interventions to identify effective ways to retain first‐time donors. STUDY DESIGN AND METHODS: The study was conducted on 1356 first‐time blood donors at four main blood centers in Iran. The donors were randomly assigned based on different interventions (phone calls, educational letter, emotional letter, incentive, motivational meeting, and no intervention) to six groups. The return rate of donors was defined as a second attempt to donate within 6 months after the first donation. Return rate and 95% confidence intervals (CIs) were calculated and compared among different groups. RESULTS: A total of 394 (29%) donors returned within 6 months for a second donation (95% CI, 0.26‐0.31). The return rate in the emotional letter group, educational letter, phone reminder, incentives, motivational meeting, and control groups was 36% (95% CI, 0.31‐0.42), 33.2% (95% CI, 0.27‐0.38), 31.5% (95% CI, 0.25‐0.37), 30% (95% CI, 0.22‐0.38), 22% (95% CI, 0.17‐0.27) and 22.1% (95% CI, 0.17‐0.27), respectively. CONCLUSIONS: This study provides evidence supporting the fact that more first‐time blood donors can be motivated to donate again by implementing targeted interventions. It demonstrates that emotional letters, educational letters, and phone reminders were effective in improving the return rate of first‐time donors.